2007
DOI: 10.1002/ejlt.200600289
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of triacylglycerol composition, melting properties and polymorphic behavior of palm oil and fractions

Abstract: Comparative analysis of triacylglycerol composition, melting properties and polymorphic behavior of palm oil and fractionsPalm oil is without doubt the most widely fractionated oil. Dry fractionation is based on differences in the melting points of triacylglycerols (TAG) which will crystallize selectively during the cooling process. Unfortunately, limitations due to intersolubility, closely linked to polymorphism, induce formation of co-crystals at each crystallization step. For this reason, only restricted TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
50
1
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 14 publications
7
50
1
6
Order By: Relevance
“…Three sub-peaks can be observed in the first melting event in the range from 0 to 9°C. Braipson-Danthine and Gibon [41] found that the relative intensity of these sub-peaks is variable, while their positions are related to the TAG composition of the PO, where the first and second sub-peaks are related to the SUU content, and third sub-peak might be related to the SUS content. We can observe a broad peak in the second melting event.…”
Section: Melting and Polymorphic Behaviormentioning
confidence: 99%
“…Three sub-peaks can be observed in the first melting event in the range from 0 to 9°C. Braipson-Danthine and Gibon [41] found that the relative intensity of these sub-peaks is variable, while their positions are related to the TAG composition of the PO, where the first and second sub-peaks are related to the SUU content, and third sub-peak might be related to the SUS content. We can observe a broad peak in the second melting event.…”
Section: Melting and Polymorphic Behaviormentioning
confidence: 99%
“…5f . Changes in polymorphic structure after fractionation have been observed with other fats such as palm oil 26 and milk fat 6 mainly due to differences in compositions and configurations of the fatty acids and TAGs 23 . The lack of influence of the fractionation conditions on the polymorphism of CNO fractions reported in this work may have lied in the fact that CNO has β -2 as a stable polymorph as already mentioned.…”
Section: Polymorphismmentioning
confidence: 99%
“…Cerretani et al adopted partial least square regression in DSC thermal analysis and quantified the fatty acid composition in olive oil [9]. Other authors found a clear relationship between TAG composition and DSC properties of olive oil and palm oil [10,11]. Haryati et al determined the IV of palm oil by DSC on the basis of bond energy [12].…”
Section: Introductionmentioning
confidence: 97%